Maternal characteristics and their relation to early mother-child interaction and cognitive development in toddlers. - Jasmin Preiß; Adelheid Lang; Theresa Hauser; Monika Angerer; Peter Schernhardt; Manuel Schabus (PLoS ONE)
Early mother-infant interaction is believed to have a significant impact on the social, cognitive, and emotional development of children. These interactions are not only influenced by child and contextual factors but also by the mother's personality traits and strain. In this study, we investigated the relation between maternal factors such as personality, depressive symptoms, or experiencing of emotions, and (i) children's early cognitive development and (ii) interaction patterns in a sample of 116 mother-child dyads (mean child age = 18.63 months ± 6.42). Maternal factors were assessed using standardized questionnaires and toddlers' cognitive development was measured using the Bayley Scales of Infant and Toddler Development. Interaction patterns were evaluated using the CARE-Index. The study found that children of mothers who scored higher in agreeableness, a personality trait reflecting compassion and cooperation, performed better in cognitive assessments. Additionally, mothers who placed significant importance on their bodily signals to assess their overall well-being had higher scores in the quality of interaction with their child. Statistical trends suggested that mothers with higher levels of conscientiousness, indicative of being organized and responsible, tended to be more responsive in the interaction with their infants, while those with higher levels of neuroticism, characterized by a tendency towards negative emotions, were more likely to have toddlers who inhibit their true negative affect. Finally, there was a trend indicating that maternal depression was associated with increased maternal controlling behavior towards toddlers. Overall, these findings show the intricate relation between maternal behavior and state with dyadic interaction quality. This should underline that optimal infant development is only possible if mothers are well supported especially if in need due to various burdens such as depressive symptoms.